HUKUM YANG HIDUP SEBAGAI SUMBER PEMIDANAAN BERLANDASKAN PANCASILA DAN HAK ASASI MANUSIA - Arliman S, Laurensius; Hutajulu, Andreas Fransiskus (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: The principle of legality in Indonesian criminal law has undergone significant development following the enactment of Law Number 1 of 2023 on the Criminal Code, particularly through the recognition of law living within society as regulated in Article 2. This regulation marks a paradigm shift from a purely formal understanding of the principle of legality toward a more material and contextual approach, while still maintaining legal certainty as a fundamental principle. This research aims to analyze the juridical construction of the recognition of living law as a basis for criminal punishment and its position within the Indonesian criminal law system. The research method employed is normative legal research using a historical legal approach, which examines the development of the principle of legality and its integration with social and constitutional values. The findings indicate that living law is recognized in a limited and conditional manner, insofar as it is consistent with Pancasila, the 1945 Constitution of the Republic of Indonesia, human rights, and general principles of law recognized by civilized nations. Its position is complementary to written criminal law, functioning to fill legal gaps and to realize substantive justice. Accordingly, this regulation reflects the state’s effort to balance legal certainty, social justice, and the protection of human rights in the reform of the national criminal law system.Keywords: Punishment, Pancasila, Human Rights.